Visualisasi Pawongan Dalam Tradisi Melayangan - I Gede Herman Saputra (Pramana: Jurnal Hasil Penelitian, 2023)
The purpose of this article is to get to know, and understand more deeply about the visualization of pawongan in the float tradition. The method used to determine the visualization of pawongan in the floating tradition in this article is to use the literature review method. Flying is a Balinese ancestral heritage, especially for people who work as farmers, kites are a form of gratitude because they are usually played after the harvest. The discussion regarding the visualization of pawongan in the flying tradition shows that: 1) Flying as a tradition in Bali has a lot of shared values. Starting from the manufacturing process even to the process of flying it or hovering; 2) The creation of works of art in the form of traditional kites in Bali cannot be separated from the customs of the Balinese agrarian community; 3) Kite festivals support the creativity of the Balinese people and indirectly become one of the efforts to preserve Balinese kites.